Phosphoribosyl Transferase (URA5) Enzyme-Mediated Detoxification of Patulin in Apple Juice and Its Effects on Nutritional Quality - Mapheto, Kopano; Akinmoladun, Oluwakamisi Festus; Maphaisa, Tiisetso Colleen; Njobeh, Patrick Berka (Indonesian Association of Food Technologists, 2025)
Patulin (PAT), a mycotoxin primarily produced by Aspergillus and Penicillium species, is a major contaminant in apple fruits and their derived products, posing significant health risks. The use of biocontrol approaches has gained attention due to their efficiency and minimal impact on product quality. This study investigated the enzymatic degradation of patulin by recombinant Orotate phosphoribosyltransferase and how it affects the nutritional properties of patulin-spiked apple juice. Apple juice samples were artificially spiked with patulin at concentrations of 100 µg/L and 250 µg/L and treated with the enzyme (0.1 mg/mL) at 36 °C for up to 24 hours. Post-treatment analysis included physicochemical properties such as pH, total soluble solids (TSS), acidity, viscosity, ascorbic acid content, total phenolic content, and amino acid composition. The enzyme-treated samples exhibited statistical reductions (P<0.05) in pH, TSS, ascorbic acid, and viscosity. Although decreases were observed in citric acid and total phenol content, these changes were not statistically significant. Among the amino acid fractions, isoleucine, leucine, arginine, proline, and serine remain unaffected (P>0.05), while a subset of essential and glucogenic amino acids showed statistically significant increases (P<0.05) in the treated sample. This study highlights the potential of enzymatic bioremediation as a safe and viable alternative for mitigating patulin contamination in fruit-based beverages. However, further studies are needed to confirm its efficacy and safety under industrial conditions.